Comparison of serotonin and dopamine release in substantia nigra and ventral tegmental area: region and species differences. - Cragg, S; Hawkey, C; Greenfield, SA (1997)
In this study, we compare the electrically evoked, somatodendritic release of dopamine (DA) with axonal release of serotonin (5-HT) in the substantia nigra (SN) and ventral tegmental area (VTA) in vitro by using fast-scan cyclic voltammetry with carbon-fibre microelectrodes. Furthermore, we have examined transmitter release in these regions in guinea-pig compared with rat. Somatodendritic DA was released, as shown previously, in guinea-pig VTA, SN pars compacta (SNc), and occasionally in SN pars reticulata (SNr). 5-HT was rarely released, except in SNr, where nonetheless it only contributed to <30% of amine signals. In rat midbrain, somatodendritic DA release was evoked to a similar extent as in guinea-pig. However, a clear species difference was apparent; i.e., 5-HT and DA were detected equally in rat SNc, whereas in rat SNr, 5-HT was the predominant transmitter detected. Nevertheless, electrically evoked extracellular concentrations of 5-HT in SNc and SNr were, respectively, seven- and fourfold less than DA in SNc. 5-HT release was low in all regions in neonatal rat slices before the maturation of 5-HT terminals. Hence, axonal 5-HT transmission in midbrain exhibits both species and site selectivity. Moreover, whereas somatodendritic DA release is conventionally regarded as modest compared with axon terminal release in striatum, somatodendritic DA release can result in significantly greater extracellular levels than a transmitter released from axon terminals in the same locality.